2021
DOI: 10.1136/bmjopen-2020-045600
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of hospitalists’ procedural skills: baseline competence and durability after simulation-based training

Abstract: ObjectivesHospitalists are expected to be competent in performing bedside procedures, which are associated with significant morbidity and mortality. A national decline in procedures performed by hospitalists has prompted questions about their procedural competency. Additionally, though simulation-based mastery learning (SBML) has been shown to be effective among trainees whether this approach has enduring benefits for independent practitioners who already have experience is unknown. We aimed to assess the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…It was deemed unethical to request students to perform venipuncture on actual patients with training limited to SBPT on venipuncture one year ago. Thus, we expected a skill decay in accordance with previous research [ 70 , 71 ]. Hence, to overcome the ethical issues arising from requesting students (who only had SBPT on venipuncture one year ago and thus, deemed not to have adequate exposure) to perform venipuncture on actual patients, we designed the study so that the students were given four weeks of clinical training where they would be able to perform venipuncture on actual patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It was deemed unethical to request students to perform venipuncture on actual patients with training limited to SBPT on venipuncture one year ago. Thus, we expected a skill decay in accordance with previous research [ 70 , 71 ]. Hence, to overcome the ethical issues arising from requesting students (who only had SBPT on venipuncture one year ago and thus, deemed not to have adequate exposure) to perform venipuncture on actual patients, we designed the study so that the students were given four weeks of clinical training where they would be able to perform venipuncture on actual patients.…”
Section: Discussionsupporting
confidence: 88%
“…They concluded that the students were able to retain the skills learned through simulation-based training for one year despite the lack of training in between. However, more recent studies have shown evidence of steep skills decay following SBPT [ 70 ], with recommendations for booster training at intervals to maintain procedural competency [ 65 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…It utilizes "active" teaching techniques and ensures competency-based education (Issenberg et al, 2005). It has enhanced learner competence and expertise (Bamford et al, 2018;Greif et al, 2010;Hale et al, 2021;Hayden et al, 2014). Due to these findings, evidence supports the introduction of SBPT to students before clerkships (Battaglia et al, 2021;Omori et al, 2005) to better prepare them to learn in the clinical setting (Battaglia et al, 2021;Remmen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Simulation-based research conducted over decades is ripe with evidence supporting improved educator and learner satisfaction (Bradley, 2006), learner knowledge and confidence (Battaglia et al, 2021;Laschinger et al, 2008), and competence when assessed on simulators (Hale et al, 2021;Morgan & Cleave-Hogg, 2000). Although most studies support the use of simulation for improved knowledge and skill, only a few studies have shown the effectiveness of transferring knowledge and skill gained in simulation training into clinical practice (Hill et al, 2011).…”
Section: Effectiveness Of Simulation For Acquiring Procedural Expertisementioning
confidence: 99%